Raymond Burr (1973 Commencement) (1973)
[00:00:00] Bands finishes playing, audiences applauds as Robert E. Kennedy takes the stage [00:00:18] Robert E. Kennedy introduces TV personality Raymond Burr and his accomplishments [00:01:19] Kennedy talks about Burr's interest in Cal Poly Rose Parade Floats [00:01:24] Kennedy talks about Burr's interests and connections with Cal Poly [00:02:25] Kennedy relates the various jobs Burr has had to all the possible careers for Cal Poly students [00:03:22] Kennedy welcomes Burr on to the stage [00:04:25] Burr speaks on the commencement as a beginning [00:07:40] Burr uses sports analog to compare to overcoming obstacles in life [00:09:38] Burr says it is important to not mistake the spectator with the sport [00:11:55] Burr says winning is the point of 'the game' [00:12:40] He states that the largest winners are the Peace Corps and foreign students [00:13:45] Burr talks about his friend who played a chief of a hospital for so long [00:15:50] Burr talks about how important it is to be flexible to be a winner [00:04:30] Burr says he learned a lot about winning from his works [00:18:33] Burr reinforces the idea that no one can help you except for yourself [00:19:25] Finishes the speech [00:20:50] Glee Club sings 'The Lord Is My Shepherd' [00:24:03] Glee Club sings 'Oh Shenandoah' [00:26:16] Glee Club sings 'Honor, Honor' [00:28:20] Robert E. Kennedy talks about H.P. Davidson, introduces former student from Glee Club, Roy Brophey [00:28:40] Davidson is brought up on stage to his surprise and Roy Brophey talks about his impact on students and the university [00:30:40] Brophey reads that building is being renamed after H.P. Davidson [00:31:42] Brief cut in tape from switching between side 1 and side 2 [00:32:40] Davidson thanks everyone